The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1074/jbc.ra120.014138
|View full text |Cite
|
Sign up to set email alerts
|

Functional impact of a congenital stationary night blindness type 2 mutation depends on subunit composition of Cav1.4 Ca2+ channels

Abstract: Voltage-gated Cav1 and Cav2 Ca2+ channels are comprised of a pore-forming a1 subunit (Cav1.1-1.4, Cav2.1-2.3) and auxiliary β (β1-4) and α2δ (α2δ-1-4) subunits. The properties of these channels vary with distinct combinations of Cav subunits and alternative splicing of the encoding transcripts. Therefore, the impact of disease-causing mutations affecting these channels may depend on the identities of Cav subunits and splice variants. Here, we analyzed the effects of a congenital stationary night blindness type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…While some found that cones are spared 13 , 17 , 31 , 55 , 56 , other reported drastic changes compared to rods 14 , 27 . Still, a recent study showed that the Ca V 1.4.IT mutation can exert different functional phenotypes depending on splice variant and subunit composition 57 . Deeper knowledge about the channel composition in rods and cones will therefore be essential to elucidate the CSNB2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…While some found that cones are spared 13 , 17 , 31 , 55 , 56 , other reported drastic changes compared to rods 14 , 27 . Still, a recent study showed that the Ca V 1.4.IT mutation can exert different functional phenotypes depending on splice variant and subunit composition 57 . Deeper knowledge about the channel composition in rods and cones will therefore be essential to elucidate the CSNB2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…For example, I745T causes Cav1.4ex47 to activate at even more negative voltages and to deactivate with slower kinetics as compared to Cav1.4+ex47. Moreover, I745T causes a breakdown in the Ca 2+ selectivity of Cav1.4ex47 but not in Cav1.4+ex47 (Williams et al 2020). Because Cav1.4ex47 is expressed in human but not in rodent retina (Haeseleer et al 2016), the I745T knock-in mouse strain (Knoflach et al 2013, Liu et al 2013b, Regus-Leidig et al 2014 might not reflect some of the pathological sequelae of the mutation in the context of Cav1.4ex47.…”
Section: Cabp4 and Alternative Splicing As Modifiers Of Cacna1f Mutationsmentioning
confidence: 99%
“…This has been studied for the Cav2.1 FHM1 variant T666M (2 residues N-terminal of the selectivity filter glutamate; Hans et al, 1999;Tottene et al, 2002). Mutations in the activation gate formed by the cytoplasmic ends of the S6 helices also affect ion selectivity and single channel conductance (e.g., Cav2.1-V714L, Cav1.4-I756T in IIS6; Figure 3; Hans et al, 1999;Tottene et al, 2002;Williams et al, 2020). A dramatic effect on ion selectivity has recently been reported for CACNA1F mutation I756T (Figure 3), which depends on C-terminal splicing and the associated β-subunit isoform (Williams et al, 2020).…”
Section: Common Macroscopic Gating Changes Induced By Protein-coding mentioning
confidence: 99%